Towards a Greener Economy in Uzbekistan - World Bank (Washington, DC, 2022)
This report is an extended Country Environmental Assessment that identifies key issues and priorities for action as Uzbekistan transitions to a sustainable and inclusive market economy. Land degradation, water stress, and air pollution from particulate matter are the main environmental issues, with additional socio-economic risks to the country from its high energy and carbon intensity and the impact of climate change on vulnerable communities. The report analyzes strategies for greening the economic transition, including resource efficiency and landscape restoration, the low-carbon transition, resilience against natural disasters and climate change, urban air quality and sustainable cities, green employment and public institutions, and green finance. Additional follow-up studies to inform detailed policy formulation and action include distributional analysis, adaptation strategy and planning, a Long-Term Decarbonization Strategy, and Climate Change Institutional Assessment, among others.